Mortars - Hogg, Ian V. 1926- (The Crowood Press, 2001)
A lively text illustrated with a wide range of archival and modern photography covers the development and deployment of mortars from their beginnings as siege weapons to the high-tech present. Includes coastal mortars, trench mortars, modern mortars and mortar ammunition.